DAMPAK KEBIJAKAN PEMANGKASAN PRODUKSI MINYAK DUNIA OLEH ORGANIZATION OF THE PATROLEUM EXPORTING COUNTRIES (OPEC) TERHADAP INDONESIA TAHUN 2016 - Ilahi, Ridho (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is about Organization of the Petroleum Exporting Countries (OPEC) as organization that have obligation to keep production to be stabilize and world petroleum pricing that have to be focussed for obligation that have been out by OPEC for cuts the world production petroleum in 2016 to stabilize the world petroleum prices and the impact that affect Indonesia as one of the member of OPEC.This research is using neo-realism perspective, in this perspective, in this perspective of neorealism or so-called structural realism emphasizes the existence of structures in viewing the phenomenon of internasional relation. How the interest with the impact of world petroleum production trimming policy by Organization of the petroleum exporting countries (OPEC) for Indonesia Backed by the International organization that is level analysis and Theory of Foreign Policy by Rosenau. The concept leads to qualitative methods and library research for references.The policy that have been out by OPEC in 2016 that focusing to increase the world petroleum prices that turn out to be costs by world petroleum exporter is to cut world petroleum production OPEC 1,2 million barrel. From the fact that have been out by OPEC , Indonesia’s domestic world petroleum been cut 5% from total Indonesia petroleum 37.000 barrels in one day. The policy that have been out by OPEC make Indonesia takes decision to suspend from Opec member to avoid the OPEC policy that makes Indonesia costs and be incompatible with Indonesia national interest.Keywords: OPEC, National Interest, Trimming,Foreign Policy